Energy Security and Energy Poverty in Emerging Economies: A Step Towards Sustainable Energy Efficiency - Nasir, Muhammad Hamid; Wen, Jun; Nassani, Abdelmohsen A.; Haffar, Mohamed; Igharo, Amechi Endurance; Musibau, Hammed Oluwaseyi; Waqas, Muhammad (Frontiers in Energy Research, 2022)
This paper presents the energy security, energy poverty, and mediating role of environmental tax policy. The environmental tax policy affects energy consumption and energy poverty. The research applied multiple, comprehensive, and relevant sets of indicators to measure energy security, energy poverty, and environmental consideration of energy poverty through environmental tax. The study used a mathematical composite indicator and an econometric estimation to conduct an empirical estimation. The study used annual data from 1990 to 2018 and concluded that long-run associations between energy security, energy poverty, and environmental tax have been characterized by the linear and asymmetric association to specify hidden cointegration behavior among the trilemma. The results show how policymakers have clouded the decision to implement appropriate energy security to mitigate energy poverty in Vietnam through environmental tax.Results show that from 2001 to 2016 in Vietnam, energy security was low and energy poverty was high, but after 2016, it can be seen that there is a dramatic change in energy security and energy poverty. The year 2018 shows the highest energy security index score (0.92) and the lowest energy poverty index score (0.12). Since 2017, Vietnam’s rural electrification plan has provided electricity to 100% of Vietnam’s population. The plan provides electricity access to 82 million people who traditionally have no grid access.